Pengaruh Manajemen Kesehatan dan Keselamatan Kerja terhadap Pelaksanaan Praktik Las - Mona Syafriani; Nurjanah, Tarbiyah; Rizta, Sri Utami (Universitas Hang Tuah Pekanbaru, 2025)
Various welding accident cases indicate hazardous conditions, highlighting the need for occupational health and safety management training for students at SMKN 2 Pekanbaru. This study adopts a quantitative, cross-sectional design, using a survey of all 39 students in the 12th-grade welding department. The study adopts a non-probability sampling method, using saturated sampling. Data were collected using a questionnaire to assess students' understanding of occupational health and safety management in welding practices. The study analyzes the data using multiple linear regression processed through SPSS. The results show that there is no partial effect of health management on the implementation of welding practices, as the t statistic < the t table value (2.055 < 2.208). At the same time, occupational safety affects the implementation of welding practices (4.598 > 2.208). Additionally, there is a simultaneous effect (F test) of health management and occupational safety on the implementation of welding practices, where F count > F table (15.330 > 3.25). Health management does not influence welding practices, whereas occupational safety does. It is advisable to provide health management training and conduct regular occupational safety training before students begin welding practices.